2018
DOI: 10.15252/emmm.201809712
|View full text |Cite
|
Sign up to set email alerts
|

CSF progranulin increases in the course of Alzheimer's disease and is associated with sTREM 2, neurodegeneration and cognitive decline

Abstract: Progranulin (PGRN) is predominantly expressed by microglia in the brain, and genetic and experimental evidence suggests a critical role in Alzheimer's disease (AD). We asked whether PGRN expression is changed in a disease severity‐specific manner in AD. We measured PGRN in cerebrospinal fluid (CSF) in two of the best‐characterized AD patient cohorts, namely the Dominant Inherited Alzheimer's Disease Network (DIAN) and the Alzheimer's Disease Neuroimaging Initiative (ADNI). In carriers of AD causing dominant mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 105 publications
0
71
2
1
Order By: Relevance
“…However, clinical manifestations of GRN mutations can also extend to AD 63 . The possibility of using progranulin as an AD biomarker was recently investigated in a large population of patients with familial and late-onset sporadic AD (Dominant Inherited Alzheimer's Disease Network and Alzheimer's Disease Neuroimaging Initiative cohorts) 64 . The CSF levels of progranulin were reportedly increased 10 years before the clinical onset of disease in AD mutation carriers.…”
Section: Progranulinmentioning
confidence: 99%
See 2 more Smart Citations
“…However, clinical manifestations of GRN mutations can also extend to AD 63 . The possibility of using progranulin as an AD biomarker was recently investigated in a large population of patients with familial and late-onset sporadic AD (Dominant Inherited Alzheimer's Disease Network and Alzheimer's Disease Neuroimaging Initiative cohorts) 64 . The CSF levels of progranulin were reportedly increased 10 years before the clinical onset of disease in AD mutation carriers.…”
Section: Progranulinmentioning
confidence: 99%
“…The CSF levels of progranulin were reportedly increased 10 years before the clinical onset of disease in AD mutation carriers. In patients with sporadic AD, increased CSF levels of progranulin were evident when neurodegeneration developed 64 . Increased levels of progranulin in CSF were also detected in suspected non-AD pathophysiology (SNAP) cases (i.e., normal Aβ biomarkers despite abnormalities in tau or neurodegeneration biomarkers; A −/TN+ 4 ) 64 .…”
Section: Progranulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma sTREM2 was significantly elevated in DS, in agreement with previously described elevation of sTREM2 in DS sera from young adults with DS prior to dementia onset 33 . Interestingly, sTREM2 is elevated in cerebrospinal fluid in the mild cognitive impairment stage of AD and in early onset forms of AD, but not in peripheral biofluids, such as plasma 24,25,27,28,54 . The elevation of sTREM2 in young DS pre-dementia in plasma and sera suggests that peripheral sTREM2 may increase very early in individuals with elevated Aβ.…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported that levels of multiple in ammatory markers (e.g., soluble tumor necrosis factor receptor [sTNFRs], intercellular cell adhesion molecule-1 [ICAM1], and vascular cell adhesion molecule-1 [VCAM1]) in the cerebrospinal uid (CSF) were signi cantly elevated in AD patients compared to healthy controls [9]. Interestingly, CSF PGRN was also found to be increased over the course of AD [10]. However, little is known about the associations of PGRN with these neuroin ammation markers.…”
Section: Introductionmentioning
confidence: 99%